Environmental Quality of forest remnants in the Capivari River Sub-basin (Campinas - Sao Paulo - Brazil) - Silva, Alessandra Leite Da [UNESP]; Ribeiro, Admilson Írio [UNESP]; Longo, Regina Márcia (Editora da Universidade Federal de Uberlândia - EDUFU, 2021)
The forest remnants present a relevant multi-functionality for the provision of ecosystem services to cities, especially the ones related to water availability in quantitative and qualitative terms, since they contribute to the control of runoff and floods, reduction of water filtration pollution, among others. Therefore, the present study aimed to assess the environmental quality of the forest remnants of the Capivari River sub-basin, in Campinas-SP, which has high water potential, by using landscape metrics. The analyzes were performed in ArcGIS on the following metrics: AREA, CAI, CI, ENN, PROXFLOW, WAT, SUR, EROD, applied for the calculation of the Environmental Quality Index (IQrem). It was identified that 78.0% of remnants have medium environmental quality, followed by 15.2% with low quality and only 6.8% with high quality. This condition is mainly related to the predominance of remnants with little or no central area, associated with predominantly elongated shapes and the distribution of these remnants in a predominantly anthropized mesh. On the other hand, these remnants have considerable connectivity, since more than 50% are close to a neighboring remnant within 60 m. A key point identified is the fact that 93.2% of the remnants are distant up to 60 m from some watercourse. Thus, it was found that the forest remnants play a significant role in maintaining water availability for the municipality of Campinas, in terms of quality and quantity. This increases the importance of carrying out effective management actions that contribute to increasing and ensuring the environmental quality of these remnants.
Keywords: Municipal water availability; Forest fragments; Environmental quality; Geoespatial indicators